Pengaruh Penggunaan E-Commerce, Modal Usaha, dan Penggunaan Sistem Infromasi Akuntansi Terhadap Kinerja Keuangan UMKM di Kota Padang - Fausiatunnisa Fausiatunnisa; Nurul Fauzi; Endrawati Endrawati (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
The purpose of this study was to determine the effect of the use of E-commerce, business capital, and the use of accounting information systems on the financial performance of UMKM in Padang City. This study uses a quantitative method with a survey approach. To obtain data in this study by distributing questionnaires. The population in this study were all micro and small business actors in Padang City. The sampling technique used in this study was purposive random sampling. The data obtained for the online questionnaire were 8 respondents and direct distribution was 105 respondents. The results of this study are the use of e-commerce and business capital have a significant positive effect on financial performance, the use of accounting information systems does not have a significant positive effect on financial performance. Together the use of e-commerce, business capital, and the use of accounting information systems have an effect on financial performance